The drivers of facility-based immunization performance and costs. An application to Moldova. (7th May 2015) - Maceira, Daniel; Goguadze, Ketevan; Gotsadze, George
Highlights: We identify production and costs determinants at the facility level as well as at the district and the national level in the Moldavian immunization program. We show the presence of economies of scale in the production of immunized population. The input prices for labor and capital reveal non-conclusive influence on the immunization costs, characteristic of a centralized program. The share of time spent by staff at health centers is a driving component in explaining immunization coverage, followed by infrastructure indicators. Abstract: Objective : This paper identifies factors that affect the cost and performance of the routine immunization program in Moldova through an analysis of facility-based data collected as part of a multi-country costing and financing study of routine immunization (EPIC). Methods : A nationally representative sample of health care facilities (50) was selected through multi-stage, stratified random sampling. Data on inputs, unit prices and facility outputs were collected during October 3rd 2012–January 14th 2013 using a pre-tested structured questionnaire. Ordinary least square (OLS) regression analysis was performed to determine factors affecting facility outputs (number of doses administered and fully immunized children) and explaining variation in total facility costs. Results : The study found that the number of working hours, vaccine wastage rates, and whether or not a doctor worked at a facility (among other factors) were positively and significantly associated with output levels. In addition, the level of output, price of inputs and share of the population with university education were significantly associated with higher facility costs. A 1% increase in fully immunized child would increase total cost by 0.7%. Conclusions : Few costing studies of primary health care services in developing countries evaluate the drivers of performance and cost. This exercise attempted to fill this knowledge gap and helped to identify organizational and managerial factors at a primary care district and national level that could be addressed by improved program management aimed at improved performance.